Genes and cells therapy - Habib, Nagy (Henry Stewart Talks, 2007)
The use of human autologous stem cells in patients that suffer from liver diseases, Stem cells specialize in repairing damaged tissues and regenerating damaged organs, Omnicyte is a particular type of CD34+ hematopoietic stem cell, Hematopoietic stem cells ability to expend and proliferate, Expression of genes associated with the hepatocyte cells phenotype, The effect of injecting human autologous stem cells into patients with liver insufficiency, Normalization of albumin and bilirubin levels in patients with liver disease, Results of phase II clinical trials